‘Maybe complicated is a better word’: Second-language English graduate student responses to syntactic complexity in a genre-based academic writing course - J. Elliott Casal; Xiaofei Lu (International Journal of English for Academic Purposes)
This practice-oriented exploratory study reports student perceptions and potential benefits of introducing syntactic complexity-focused activities in an advanced English for Academic Purposes writing course. Syntactic complexity, seen by many as a multidimensional construct and generally defined as the range and sophistication of structures used, is here operationalized through four approaches. The pedagogical site was a six-week mixed-discipline writing course with an emphasis on second-language English research writing. Attention to syntactic complexity was integrated into a previously established corpus- and genre-analysis based pedagogy, and data is comprised of a learner-perception survey and interview and instructor observational journals. Emphasis was placed on reflection on complexity in academic writing, rather than the production of complex structures. The findings suggest benefits for targeted instruction of syntactic complexity in all four categories, with particular benefits to student writer confidence and intentionality resulting from increased awareness of the affordances and appropriateness of complexity overall.